Orthokeratinized odontogenic keratocyst crossing mandibular midline: A diagnostic dilemma - Kapil Kshirsagar; Sonal Shah; Supriya Kheur (Medical Journal of Dr. D.Y. Patil University, 2014)
Orthokeratinized odontogenic keratocyst is a less-aggressive non-syndromic variant of odontogenic keratocyst (OKC). In this case report, we are highlighting an unusual presentation of OKC with paresthesia, non-vital teeth, and minimal cortical expansion. The radiograph of the patient revealed a radiolucency crossing the midline in the anterior mandible. This manuscript discusses a case which presented as a diagnostic dilemma due to variable clinical and radiological features mimicking different pathologies occurring in the anterior mandible. We have discussed various clinical and radiographic differential diagnoses of the same.